Effect of supplemental Kluyveromyces marxianus and Pichia kudriavzevii on aflatoxin M1 excretion in milk of lactating dairy cows - Malinee Intanoo (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. The objective of this study was to determine the effect of supplementing Kluyveromyces marxianus CPY1, K. marxianus RSY5 and Pichia kudriavzevii YSY2 isolated from ruminal fluid of dairy cows on transfer of aflatoxin B1 (AFB1) from feed into aflatoxin M1 (AFM1) in milk, DMI, milk production and nutrient digestibility. Four multiparous Holsteins in mid-lactation were used in a 4 × 4 Latin square design trial consisting of 14 days in each experimental period for sample collection. Between each period, 14 clearance days prior to the next treatment were allowed to minimize carryover effects. In each treatment, subsequent supplementation of isolated yeast was compared, i.e., (1) control (without yeast supplementation), (2) K. marxianus CPY1 (K1Y), (3) K. marxianus RSY5 (K2Y) and (4) P. kudriavzevii YSY2 (PY). All diets contained 22.28 µg of AFB1/kg. Treatments were individually fed at the rate of 2 g/day (1 × 109 CFU/g) of yeast biomass or corn meal in the control group. Concentrations of AFM1 in milk was reduced with yeast and averaged 1.54, 0.36, 0.43 and 0.51 µg/L for control, K1Y, K2Y and PY, respectively (p < 0.01). The transfer of AFB1 from feed into AFM1 in milk was higher in control compared with K1Y, K2Y and PY (7.26% vs. 1.18%, 1.44% and 1.69% respectively, p < 0.01). Supplementation of yeast also improved DMI and milk compositions, but no differences were observed in nutrient digestibility or milk yield among treatments. Concentration and yield of milk protein, fat, lactose, solid-not-fat (SNF) and total solids were greater in cows fed yeast compared with the control (p < 0.01). These results indicate that K. marxianus CPY1, RSY5 and P. kudriavzevii YSY2 shows promise as a dietary supplementation to detoxify AFB1 and improve DMI and yield of milk components.